Optimizing prevention and community-based management of severe malnutrition in children. - Zulfiqar A Bhutta (PLoS Medicine, 2022)
Zulfiqar A. Bhutta discusses prevention and treatment strategies for optimization of community-based management of severe acute malnutrition in children.